Cleavage of the soluble (pro)renin receptor (sATP6AP2) in the placenta. (November 2020) - Morosin, Saije K.; Delforce, Sarah J.; Lumbers, Eugenie R.; Pringle, Kirsty G.
Abstract: Introduction: The (pro)renin receptor (ATP6AP2) is cleaved and released as soluble ATP6AP2 (sATP6AP2). The sATP6AP2 is detected in plasma and urine and is elevated in women with gestational diabetes and preeclampsia. The source and cleavage pathway of sATP6AP2 in pregnancy is unknown. The syncytiotrophoblast is the major placental secretory layer and is in direct contact with maternal blood. Both FURIN and Site 1 protease (MBTPS1) cleave sATP6AP2 in non-placental cells. We postulated that ATP6AP2 was cleaved by FURIN and/or MBTPS1 and that sATP6AP2 is secreted by the placental syncytiotrophoblast. Methods: Term primary trophoblast cells were transfected with FURIN siRNA, negative control siRNA or vehicle. In a separate experiment, primary trophoblasts were treated with a pro-protein convertase inhibitor (DEC-RVKR-CMK), an MBTPS1 inhibitor (PF 429242) or vehicle. Trophoblasts were left to spontaneously syncytialise before cells and supernatants were collected and intracellular and extracellular sATP6AP2 levels analysed by immunoblot. Results : sATP6AP2 is secreted by placental trophoblasts. Levels of intra and extra-cellular sATP6AP2 decrease with syncytialisation (P = 0.01 and P = 0.02, respectively), as do FURIN mRNA (P = 0.0003) and protein (P = 0.0007). FURIN siRNA decreased FURIN mRNA and protein levels (both P < 0.0001). Neither FURIN siRNA or PF 429242 affected sATP6AP2 levels. DEC-RVKR-CMK significantly decreased extracellular sATP6AP2 protein levels (P = 0.02). Discussion: Soluble ATP6AP2 is secreted by placental trophoblasts and levels decrease with syncytialisation. DEC-RVKR-CMK, a broad inhibitor of pro-protein convertases reduced extracellular sATP6AP2 levels, but FURIN siRNA and MBTPS1 inhibition had no effect. Hence, a convertase other than FURIN or MBTPS1 is most likely responsible for placental sATP6AP2 secretion. Highlights: ATP6AP2 is secreted by placental trophoblasts. sATP6AP2 levels decrease as trophoblasts syncytialise. Intracellular sATP6AP2 levels positively correlate with FURIN levels. Neither FURIN or MBTPS1 alone cleave sATP6AP2 in the placenta. A pro-protein convertase targeted by DEC-RVKR-CMK enables sATP6AP2 secretion.